Mutations in the Hco-mptl-1 gene in a field-derived monepantel-resistant isolate of Haemonchus contortus. Issue 2 (August 2017) - Bagnall, Neil H.; Ruffell, Angela; Raza, Ali; Elliott, Timothy P.; Lamb, Jane; Hunt, Peter W.; Kotze, Andrew C.
Abstract: Resistance to the anthelmintic drug monepantel (Zolvix ® ) has emerged in parasitic worms infecting sheep and goats. The mechanism of resistance in these cases is unknown. The drug targets nicotinic acetylcholine receptors belonging to the nematode-specific DEG-3 subfamily. We examined the receptor gene, Hco-mptl-1, in a highly Zolvix ® -resistant and a -susceptible isolate of the parasitic nematode Haemonchus contortus . cDNA coding for the full length receptor protein ( Hco -MPTL-1) was present in all clones prepared from a pool of susceptible larvae (21/21 clones) and approximately 50% of those from the resistant isolate (17/33). On the other hand, the remaining clones from the resistant isolate showed various mutations that resulted in truncated predicted proteins, missing at least one transmembrane domain. The most common mutation (11/33 clones) resulted in the retention of intron 15, a premature stop codon, and a truncated protein. Sequencing of intron 15 genomic DNA showed very few SNPs in susceptible larvae and in 12/18 clones from resistant larvae, alongside the presence of at least 17 SNPs in the remaining resistant clones. The present study shows that the highly resistant isolate has a number of mutations in the drug target gene that would most-likely result in a non-functional receptor, thus rendering the larvae insensitive to the drug. The presence of many wild-type sequences in this highly-resistant population suggests that there was a significant presence of heterozygotes in the survivors of the field drench treatment from which the isolate was derived, and hence that at least some of the mutations may be dominant. Alternatively, their presence may be due to the additional influence of mutations at another locus contributing to the resistance phenotype. The presence of multiple separate mutations in the Hco-mptl-1 gene in this viable field-derived worm isolate may at least partly explain why resistance to Zolvix ® has arisen rapidly in the field. Graphical abstract: Highlights: Hco-mptl-1 gene compared in susceptible and monepantel-resistant Haemonchus contortus . Six separate mutations detected in the resistant isolate. Most common mutation resulted in retention of intron and truncated predicted protein. Many separate mutations in the drug target site in the field-derived resistant isolate.